Frosting Characteristics of Horizontal Array Square Micropillar Surface under Natural Convection - Zhang Tianlei; Zhao Yanjie (Zhileng xuebao)
In this study, a micromachined array square micropillar metal surface was fabricated. Its frosting characteristics under natural convection were investigated experimentally at an ambient temperature of Tatm= 24 ℃ and relative humidity of 17%, with different cold surface temperatures Tw of ﹣5.2 ℃, ﹣10.1 ℃, and﹣15.2 ℃ and different specimen sizes. The effects of the surface temperature and time duration on the frost thickness and weight were analyzed. In addition, an antifrosting mechanism of the array square micropillar surface was proposed and validated by simulation. The results showed that when the surface temperature was -10 °C, the frost weight on the array square micropillar surface reduced by approximately 32% compared to that on a flat surface. Moreover, an air vortex was generated by natural convection, which prevented the water vapor from remaining in the groove. Frost formedonly on the top of the micropillar, rather than in the groove. The effective frosting surface was reduced significantly. When the micropillar spacing was too large, condensation droplets and frost were formed inside the groove.